"Sports is Politics": Swimming (and) Pools in Postcolonial Singapore. Issue 1 (2nd January 2016) - Chan, Ying-Kit
Abstract: Almost immediately after Singapore's independence in 1965, sports became an agent of social engineering in the creation of the new nation, and the ruling People's Action Party (PAP) government pragmatically used the institution of sports in its nation-building enterprise. Based on an analysis of the speeches and press statements of Singaporean bureaucrats and civil servants from the 1960s to the 1980s, this article investigates the ruling elite's general perception of sports and regional sporting events, examining how such a perception influenced Singapore's local governance and strategic thinking in foreign relations. Although scholars have pointed out that sports were prominent in the nationalistic discourses of Singapore and in the projection of Singapore's international image, little about the history and development of individual sports in Singapore is known. The article argues that swimming was the premier sport of choice for Singapore's ruling elite in its projects of building bodies and the nation after independence, manifested in the swimming pools that the nascent nation strove to build in the residential estates outside the "colonial stronghold" of the central town district.